Global crustal stress pattern based on the world stress map database release 2008 - Heidbach, O.; Tingay, Mark; Barth, A.; Reinecker, J.; Kurfess, D.; Mϋller, B. (Elsevier Science BV, 2009)
The World Stress Map (WSM) project is a global compilation of information on the contemporary crustal stress field from a wide range of stress indicators. The WSM database release 2008 contains 21,750 stress data records that are quality-ranked using an updated and refined quality-ranking scheme. Almost 17,000 of these data records have A–C quality and are considered to record the orientation of maximum horizontal compressional stress SH to within ±25°. As this is almost a triplication of data records compared with the first WSM database release in 1992, we reinvestigate the spatial wave-length of the stress patterns with a statistical analysis on a global 0.5° grid. The resulting smoothed global stress map displays both; the mean SH orientation that follows from the maximum smoothing radius for which the standard deviation is <25° and a countour map that displays the wave-length of the stress pattern. This smoothed global map confirms that long wave-length stress patterns (>2000 km) exist for example in North America and NE Asia. These have been used in earlier analyses to conclude that the global stress pattern is primarily controlled by plate boundary forces that are transmitted into the intraplate region. However, our analysis reveals that rather short wave-length of the stress pattern <200 km are quite frequent too, particularly in western Europe, Alaska and the Aleutians, the southern Rocky Mountains, Basin and Range province, Scandinavia, Caucasus, most of the Himalayas and Indonesia. This implies that local stress sources such as density contrasts and active fault systems in some areas have high impact in comparison to plate boundary forces and control the regional stress pattern.